2020
DOI: 10.1186/s13071-020-04401-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Kato-Katz method and real time polymerase chain reaction for the diagnosis of soil-transmitted helminthiasis in the framework of a randomised controlled trial: treatment efficacy and day-to-day variation

Abstract: Background Accurate, scalable and sensitive diagnostic tools are crucial in determining prevalence of soil-transmitted helminths (STH), assessing infection intensities and monitoring treatment efficacy. However, assessments on treatment efficacy comparing traditional microscopic to newly emerging molecular approaches such as quantitative Polymerase Chain Reaction (qPCR) are scarce and hampered partly by lack of an established diagnostic gold standard. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Since its last assessment for human helminthiases 16,17 , the tool has undergone substantial development and we aim to provide data on its applicability within the framework of this trial. Diagnostic assessment by qPCR has been recently shown by our group to be more sensitive compared to standard Kato-Katz microscopy 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its last assessment for human helminthiases 16,17 , the tool has undergone substantial development and we aim to provide data on its applicability within the framework of this trial. Diagnostic assessment by qPCR has been recently shown by our group to be more sensitive compared to standard Kato-Katz microscopy 28 .…”
Section: Discussionmentioning
confidence: 99%
“…An in-house method based on previous work from our group will be used. Details on procedures, reagents, kits and conditions have been described in a recent publication by Keller et al 28 .…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…It is inferred that qPCR could be detecting DNA from other worm specimens than the egg [ 8 , 36 , 45 ], and thus, detecting prepatent infections (immature worms not releasing eggs) [ 44 ]. Other studies found better correlation between eggs per gram and PCR results, but they were using other PCR outcomes such as DNA copies [ 38 , 43 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiparallel qPCR showed cost diminution [ 46 ] and some studies are attempting to optimize a sample pooling protocol to make qPCR surveillance more cost-effective [ 52 ]. Moreover, sample storage, DNA extraction and qPCR protocols should be harmonized [ 45 , 47 , 53 ]. In addition, an external quality assurance for reference labs should be established [ 49 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the Kato-Katz method may lead to an underestimation of the true prevalence, which in turn could result in an artificial inflation of CRs from undetected residual low-egg count infections post-treatment. Indeed, a comparison of Kato-Katz and qPCR efficacy results 14–21 days post-treatment on Pemba Island revealed significantly lower CRs for ivermectin-albendazole, when two fecal samples before and after treatment were analysed by qPCR [ 42 ]. Since the majority of participants had light infections at follow-up, our resulting apparent reinfection rates and new infections should therefore be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%